2014
DOI: 10.1007/jhep10(2014)151
|View full text |Cite
|
Sign up to set email alerts
|

A simple holographic model of a charged lattice

Abstract: Abstract:We use holography to compute the conductivity in an inhomogeneous charged scalar background. We work in the probe limit of the four-dimensional Einstein-Maxwell theory coupled to a charged scalar. The background has zero charge density and is constructed by turning on a scalar source deformation with a striped profile. We solve for fluctuations by making use of a Fourier series expansion. This approach turns out to be useful for understanding which couplings become important in our inhomogeneous backg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…We see that, if δO is proportional to − δp x , a Drude-like peak may appear [29]. Furthermore, if δO is independent of parameters(µ, T, β), the scattering time will be inversely proportional to β. i.e.…”
Section: Optical Conductivity and Coherent/incoherent Metalmentioning
confidence: 84%
See 1 more Smart Citation
“…We see that, if δO is proportional to − δp x , a Drude-like peak may appear [29]. Furthermore, if δO is independent of parameters(µ, T, β), the scattering time will be inversely proportional to β. i.e.…”
Section: Optical Conductivity and Coherent/incoherent Metalmentioning
confidence: 84%
“…AC electric conductivity was also studied in [25] and here we analyse it in greater detail as well as thermoelectric and thermal conductivities. For AC conductivities in other HBC models including massive gravity models we refer to [14,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in [33], the authors studied the optical conductivity by adding a gravitational background lattice. Other papers about holographic lattice can be viewed in [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. The DeTurck method provides a good tool for solving Einstein equations in these papers.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that the AdS plane waves describe simple backgrounds which are dual to anisotropically excited systems with energy fluxes [39]. An inhomogeneous background has been used to holographically calculate conductivity [40].…”
Section: Inhomogeneous Backgroundsmentioning
confidence: 99%